Web-based physical activity promotion in young people with CF: a randomised controlled trial. Issue 1 (30th September 2022) - Cox, Narelle S; Eldridge, Beverley; Rawlings, Sarah; Dreger, Julianna; Corda, Jennifer; Hauser, Jennifer; Button, Brenda M; Bishop, Jennifer R; Nichols, Amanda; Middleton, Anna; Ward, Nathan; Dwyer, Tiffany; et al.
Abstract : Background: Physical activity levels are known to decline following hospitalisation for people with cystic fibrosis (pwCF). However, optimal physical activity promotion strategies are unclear. This study investigated the effect of a web-based application (ActivOnline) in promoting physical activity in young pwCF. Methods: Multicentre randomised controlled trial with assessor blinding and qualitative evaluation. People with CF (12–35 years) admitted to hospital for a respiratory cause were eligible and randomised to the 12-week ActivOnline intervention (AO) or usual care (UC). The primary outcome was change in device-based time spent in moderate-to-vigorous physical activity (MVPA) from baseline to post-intervention. Follow-up was at 6 months from hospital discharge when qualitative evaluation was undertaken. Results: 107 participants were randomised to AO (n=52) or UC (n=55). Sixty-three participants (59%) contributed to the intention-to-treat analysis. Mean (SD) age was 21 (6) years (n=46, <18 years). At baseline, physical activity levels were high in both groups (AO 102 (52) vs UC 127 (73) min/day). There was no statistically significant difference in MVPA between groups at either timepoint (post-intervention mean difference (95% CI) −14 mins (−45 to 16)). Uptake of the intervention was low with only 40% (n=21) of participants accessing the web application. Conclusion: A web-based application, including individualised goal setting, real-time feedback and motivation for behavioural change, was no better than usual care at promoting physical activity in young pwCF following hospital discharge. High levels of baseline physical activity levels in both groups, and limited engagement with the intervention, suggest alternative strategies may be necessary to identify and support young pwCF who would benefit from enhanced physical activity. Trial registration number: ACTRN12617001009303, 13 July 13 2017.